فعالية استخدام الاتصال الرقمي في تحسين الأداء الوظيفي دراسة ميدانية بجامعة محمد الشريف مساعدية- سوق اهراس - - دريدي إيمان; قريميدة وفاء (My University, 2021)
Abstract: We have endeavoured through our research to be acquainted with the effectiveness of the use of digital communication in improving the performance at work, seeing that the digital communication has become one of the pillars on which are based various institutions in order to improve their performance, among which the university as a public institution of great importance in the society, which strives to achieve its own objectives throughout the improvement of the performance of its employees. Besides, the university has had to keep pace with the development and modernization of its sector by adopting digital communication that offers many advantages leading to the improvement of its services. In virtue of which, we conducted this research at the University of Mohamed-Cherif Messaadia, Faculty of Social and Human Sciences, and Faculty of Literature and Languages in the Province of Souk Ahras. In this regards, the main question focuses on: - How effective is the use of digital communication in improving performance at work? From which question arise a number of sub-questions, namely: 1) What is the nature of the digital communication environment within the university? 2) What are the effects resulting from the integration of digital communication while improving the performance at work? 3) What are the problems hindering the use of digital communication? In relation with the purpose of this study and the objectives thereof, we used the survey method and adopted a questionnaire as a basic tool in this research, and an interview as a secondary tool. Furthermore, with regards to the research sample, it included the staff of the administrations at the Faculty of Social and Human Sciences and the Faculty of Literature and Languages, intentionally according to the purposeful sampling. Through this research, we tried to identify the effectiveness of using digital communication in improving the performance at work. As a result of which, we have achieved a number of results, namely: -  Digital communication is being used by the university staff, who show wide adoption of the same, although there exist some obstacles and difficulties they are facing while using such kind of communication;  There exist positive effects on the staff performance at work when using the means of digital communication through saving their time and their deployed efforts;  Changing the work system at the university for the better levels, through digital communication by restructuring and organizing the same in such a manner to provide help in improving the global performance thereof. * Our research has recommended to pay particular attention to such type of communication by providing financial capabilities to support it, as well as providing training for all the staff in using the digital communication so as to highlight the effectiveness thereof, as this will improve their performance and achieve the goals traced by the university. --------------------------------------- ملخص: سعينا من خلال بحثنا إلى الوقوف على مدى فعالية استخدام التواصل الرقمي في تحسين الأداء في العمل، إذ أصبح التواصل الرقمي أحد الركائز التي ترتكز عليها مختلف المؤسسات لتحسين أدائها، ومن بينها الجامعة، كمؤسسة عامة ذات أهمية بالغة في المجتمع، تسعى جاهدة لتحقيق أهدافها من خلال تحسين أداء موظفيها. كما حرصت الجامعة على مواكبة التطور والتحديث في قطاعها من خلال تبني التواصل الرقمي الذي يوفر مزايا عديدة تُسهم في تحسين خدماتها. وبناءً على ذلك، أجرينا هذا البحث في جامعة محمد الشريف مساعدية، بكلية العلوم الاجتماعية والإنسانية، وكلية الآداب واللغات بولاية سوق أهراس. وفي هذا الصدد، يتمحور السؤال الرئيسي حول: - ما مدى فعالية استخدام التواصل الرقمي في تحسين الأداء في العمل؟ وينبثق من هذا التساؤل عدد من الأسئلة الفرعية، وهي: 1) ما طبيعة بيئة الاتصال الرقمي في الجامعة؟ 2) ما الآثار المترتبة على دمج الاتصال الرقمي في تحسين الأداء في العمل؟ 3) ما هي المشكلات التي تعيق استخدام الاتصال الرقمي؟ فيما يتعلق بغرض هذه الدراسة وأهدافها، استخدمنا منهج المسح، واعتمدنا الاستبيان كأداة أساسية في هذا البحث، والمقابلة كأداة ثانوية. أما عينة البحث، فقد شملت موظفي إدارات كليتي العلوم الاجتماعية والإنسانية والآداب واللغات، وذلك بشكل مقصود وفقًا للعينة القصدية. ومن خلال هذا البحث، حاولنا التعرف على مدى فعالية استخدام الاتصال الرقمي في تحسين الأداء في العمل. ونتيجةً لذلك، حققنا عددًا من النتائج، وهي: - يستخدم موظفو الجامعة الاتصالات الرقمية، ويظهرون تبنيًا واسعًا لها، على الرغم من وجود بعض المعوقات والصعوبات التي يواجهونها عند استخدامها؛ هناك آثار إيجابية على أداء الموظفين في العمل عند استخدام وسائل الاتصال الرقمية من خلال توفير وقتهم وجهدهم المبذول؛ تغيير نظام العمل في الجامعة نحو الأفضل، من خلال الاتصال الرقمي، وذلك بإعادة هيكلته وتنظيمه بما يُسهم في تحسين أدائه العام. * أوصى بحثنا بإيلاء اهتمام خاص لهذا النوع من الاتصالات من خلال توفير الإمكانات المالية اللازمة لدعمه، بالإضافة إلى توفير التدريب لجميع الموظفين على استخدام الاتصالات الرقمية لإبراز فاعليتها، مما يُحسّن من أدائهم ويُحقق الأهداف التي تسعى الجامعة إلى تحقيقها.
Keywords: الاتصال الرقمي، الأداء الوظيفي; الفعالية؛ الاتصال الرقمي؛ الرقمنة؛ الأداء في العمل